Idealized design parameters of Wave Energy Converters in a range of ocean wave climates. (September 2017) - Illesinghe, S.J.; Manasseh, R.; Dargaville, R.; Ooi, A.
Highlights: Performance effects of idealized design parameters on a generic model is investigated. Maximum power generation requires optimal damping and natural period of oscillation. Wave climates in mid-latitudes and tropics on power generation are considered. Seasonal wave climates which generate maximum power is identified. Abstract: The effect of the idealized design parameters, the natural period of oscillation and damping, on the performance of a generic Wave Energy Converter (WEC) model is investigated. Other studies have been conducted on specific WEC technologies, overlooking the impact of these design parameters. Australia has been used as a case study. The consequences of the damping parameter are highlighted. A broad range of ocean wave climates are investigated across different seasons to determine the idealized values of the parameters appropriate for a location, to assist planning for extensive WEC deployments. Swell and wind-sea wave systems were studied; the response of generic model was used to determine the theoretical power generated. It was found that WECs should be selected for a location based on their damping as well as their natural period of oscillation so that the ocean wave resource is optimally utilized.